2008
DOI: 10.1017/s1833367200003291
|View full text |Cite
|
Sign up to set email alerts
|

Influences on the provision of work–life benefits: Management and employee perspectives

Abstract: As several previous studies have shown, the provision of work–life benefits (WLB) varies between organisations; while some organisations provide a comprehensive range of WLB, others do not. Our research aims to identify and examine the influences on the provision of WLB in an organisation. Recognising the potential for different goals and agenda, we propose that it is necessary to understand the perspectives of WLB held by managers and by employees. To inform our research, we have drawn upon the complementary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 43 publications
0
9
0
1
Order By: Relevance
“…Although studies on WLB practices are often limited to small sample sizes (e.g., Bardoel et al, ; Blair‐Loy & Wharton, ), employees (Glass & Fujimoto, ), or large companies (Abbott & De Cieri, ), research has shown that SMEs typically use three to five WLB practices (Cegarra‐Leiva et al, ). However, no empirical study related to SMEs’ adoption of WLB practices exists.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Although studies on WLB practices are often limited to small sample sizes (e.g., Bardoel et al, ; Blair‐Loy & Wharton, ), employees (Glass & Fujimoto, ), or large companies (Abbott & De Cieri, ), research has shown that SMEs typically use three to five WLB practices (Cegarra‐Leiva et al, ). However, no empirical study related to SMEs’ adoption of WLB practices exists.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Abbott and De Cieri () contended that interest groups can influence policy, procedures, and business directions, and have a stake in the actions of the organization. Governments are in a particularly influential position because they legislate employment conditions, which have made WLB issues a topic of considerable national attention in Australia.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Availability of family benefits depends on a vector of workplace characteristics reflecting: (a) worker and firm characteristics and (b) characteristics of the strata where the firm is more likely to draw their employees (Abbott & De Cieri, 2008). The first group of variables includes five indicators for industry (primary industries is the reference group), four occupational indicators (production workers is the reference group), three indicators for firm size (firms with less than 20 workers is the reference group), measures of tenure and experience, three indicators for numbers of hours worked and four educational indicators (no educational degree is the omitted category).…”
Section: Family Supportmentioning
confidence: 99%
“…Abbott and De Cieri (2008) point out the main influences in the provision of benefits and develop case studies to assess these influences. Parkes and Langsford (2008) test whether satisfaction about work-family balance influences hiring and retention in Australian firms.…”
Section: Introductionmentioning
confidence: 99%